Comprehensive Analysis of Autophagy-Associated lncRNAs Reveal Potential Prognostic Prediction in Pancreatic Cancer - Chen, Guangyu; Yang, Gang; Long, Junyu; Yang, Jinshou; Qin, Cheng; Luo, Wenhao; Qiu, Jiangdong; Zhao, Fangyu; You, Lei; Zhang, Taiping; Zhao, Yupei (Frontiers in Oncology, 2021)
Pancreatic cancer (PC) is a highly malignant tumor in the digestive system. Both long noncoding RNAs (lncRNAs) and autophagy play vital roles in the development and progress of PC. Here, we constructed a prognostic risk score system based on the expression profile of autophagy-associated lncRNAs for prognostic prediction in PC patients. Firstly, we extracted the expression profile of lncRNA and clinical information from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) databases. The autophagy-associated genes were from The Human Autophagy Database. Through Cox regression and survival analysis, we screened out 7 autophagy-associated lncRNAs and built the risk score system in which the patients with PC were distinguished into high- and low-risk groups in both training and validation datasets. PCA plot displayed distinct discrimination and risk score system displayed independently predictive value for PC patient survival time by multivariate Cox regression. Then we built a lncRNA and mRNA co-expression network via Cytoscape and Sankey diagram. Finally, we analyzed the function of lncRNAs in high- and low-risk groups by gene set enrichment analysis (GSEA). The results showed that autophagy and metabolism might make significant effects on PC patients of low-risk groups. Taken together, our study provides a new sight to understand the role of autophagy-associated lncRNAs and finds novel therapeutic and prognostic targets in PC.